The Correlation between Cigarette Smoking and Salivary Flow Rate - A Alaee; A Azizi; N Valaie; SH Moieni (Islamic Azad University, 2017)
Background and aim: Side effects of cigarette smoking are among the major concerns. These complications can adversely affect the oral environment. Since reduced salivary flow rate increases the incidence of tooth decay and other dental and oral problems, the present research aimed to investigate the relationship between cigarette smoking and salivary flow rate. Materials and Methods: In this historical cohort study, 50 cigarette smokers (case) and 50 non-smokers (control) were involved, who were matched according to age and gender. Non-stimulated whole saliva was measured by using the modified Schirmer test (MST) performed between 9 a.m. and 12 p.m. by a trained examiner. All the participants refrained from eating, drinking and smoking for 2 hours prior to the study. The subjects were asked to sit in an upright position and to raise and slowly retract their tongue, to avoid unintentional wetting of the Schirmer test's strip. The strip was kept vertically with the help of cotton pliers, while the bottom of the paper was in contact with the floor of the mouth. The length of the wet area on the strip was recorded at the intervals of 1, 2 and 3 minutes. Data were analyzed with Mann-U-Whitney and Chi-square tests. Results: The quantitative value of salivary flow rate was equal to 24.8±2.4mm in controls, and 15.8±2.1mm in case group (P<0.001). 30% of non-smokers and 90% of smokers exhibited reduced salivary flow rate (P<0.000). Conclusion: It seems that reduced salivary flow rate is more significant in cigarette smokers than in non-smokers.